Temporal Partitioning of Cardiac Metabolism by the Cardiomyocyte Circadian Clock - Young, Martin E. (Exp Physiol, 2016)
Cell autonomous circadian clocks have emerged as critical mediators of twenty four hour rhythms in cellular processes. In doing so, these molecular timekeepers confer the selective advantage of anticipation, allowing cells/organs to prepare for stimuli/stresses before their onset. The heart is subjected to dramatic fluctuations in energetic demand and nutrient supply in association with sleep/wake and fasting/feeding cycles. Recent studies suggest that the cardiomyocyte circadian clock orchestrates daily rhythms in both oxidative and non-oxidative glucose and fatty acid metabolism, as well as protein turnover. Here, we review this evidence, and discuss whether disruption of these rhythms can contribute towards cardiovascular disease.